Language Use in Literature as a Reflection of Cultural Values - Muhammad Ali Imran (Proceeding of the International Conference on Global Education and Learning, 2024)
This study examines the intricate relationship between language use in literature and the cultural values it reflects. Language serves not only as a medium of communication but also as a vessel for cultural identity, beliefs, and social norms. Through a comparative analysis of literary works from diverse cultural backgrounds, this research highlights how authors employ language to convey their cultural narratives, ideologies, and ethical frameworks. The study focuses on various literary genres, including poetry, prose, and drama, to illustrate how linguistic choices—such as diction, syntax, and figurative language—embody the values and traditions of specific cultures. Additionally, the research investigates the impact of historical and social contexts on language use in literature, revealing how cultural shifts and globalization influence literary expression. By analyzing texts from different periods and regions, this study aims to demonstrate that literature not only reflects cultural values but also plays a crucial role in shaping and challenging them. Ultimately, the findings underscore the importance of understanding language in literature as a key to unlocking the deeper meanings of cultural identity and heritage.